KEMAMPUAN PEMAHAMAN MATEMATIS SISWA PASCA PANDEMI COVID-19 PADA MATERI PERSAMAAN KUADRAT KELAS IX - Sharicah Sharicah; Ratna Sariningsih (IKIP Siliwangi, 2023)
Students must have the ability to understand mathematics because learning mathematics is not only about memorizing formulas and counting, but also about understanding concepts. The purpose of this study is to determine the mathematical understanding of students after the Covid-19 pandemic with quadratic equations. This type of research is qualitative with a population of 30 students and a sample of 10 class IX students conducted at SMPN 8 Cimahi. The instrument used is a mathematical comprehension test. The data obtained from the test results are processed in three stages, namely first data reduction (analysis of student answers), second presentation, and thirdly drawing researchers' conclusions. The results showed that 10% of students who have mathematical ability belong to the very high and very low categories, 20% belong to the high and low categories, and 40% of students belong to the medium category. This research shows that students' mathematical comprehension skills still need to be developed because students still do not understand the material and are not used to doing mathematical comprehension questions so they still make mistakes when solving problems.